A framework for selecting infrastructure projects for digital twin adoption - Schneider, Paul (Nanyang Technological University, 2023)
Large infrastructure projects (LIP) encompass copious amounts of information from concept to asset operations. Managing this colossal and dynamically changing information requires substantial administrative resources. Construction managers often end up spending 30-50% of their time searching for information to control projects and make informed decisions. Unfortunately, the current approach involves an unintegrated manual process that lacks system interoperability. The implementation of efficient integrated systems in place of manual control processes has the potential to decrease schedule delays by up to 15% and project cost deviation by up to 10%. This will also minimise the need for expensive rework and dispute resolution. This challenge extends beyond the project team and affects the entire organisational value chain. Reports indicate that the engineering and construction industries can achieve productivity gains of 14-15% and cost reductions of 6-7% through effective digital transformation. The digital twin (DT) has been adopted successfully within the product manufacturing and aerospace industries over the past two decades. However, civil engineering and the built environment have traditionally lagged in technology adoption. This adoption lag may be attributed to insufficient resource allocation and funding for knowledge and technology, which generally pales in comparison to other industries. In recent years, momentum has been building globally for LIP project delivery, with significant adoption of Building Information Management (BIM) and the ISO 19650 standard supported by governments and the infrastructure sector. As a result, the sector now looks to DT adoption to build on the wave of digital transformation. This research proposes a comprehensive framework that assesses the suitability of infrastructure projects for DT technology and provides effective guidelines for implementing DT in eligible projects.